Hamstring Flexibility Is Not Correlated with Isokinetic Knee Muscle Strength in Female Modern Dancers - (:unkn) unknown (SCIENCE & MEDICINE INC, 2018)
OBJECTIVE: To evaluate bilateral isokinetic knee extensor and flexor muscle strength relative to hamstring flexibility in female modern dancers. METHODS: 20 trained university-level female modern dance students (mean age 23.8 +/- 3.8 yrs) volunteered for the study. Concentric isokinetic peak torque (PT, in Nm), peak torque % of body weight (PT% BW, in Nm/kg), and total work (TW, in J) of the knee extensor and flexor muscles for each leg were measured with a dynamometer at a velocity of 60, 180, and 300 degrees/s. Hamstring flexibility of both limbs was assessed by a goniometer with the subjects in a supine position using the active straight leg raise (SLR) test. Participants were divided into flexible (n=10) and highly flexible (n=10) groups based on their hamstring flexibility. RESULTS: The flexible and highly flexible groups had significant differences (p=0.05) for the right (flexible, 119.7 +/- 4.3 degrees; highly flexible, 137.7 +/- 2.6 degrees) and left active SLR tests (flexible, 120.6 +/- 5.3 degrees; highly flexible, 138.3 +/- 4.5 degrees). No significant differences were found between the flexible and highly flexible dancers for concentric knee extensor and flexor muscle strength in all selected parameters (p <= 0.05). There were also no significant correlations between flexibility and bilateral PT, PT% BW, and TW scores (60, 180, and 300 degrees/s) of dancers at the concentric contraction (p <= 0.05). CONCLUSION: These findings indicate that hamstring flexibility (for both the flexible and highly flexible groups) is not correlated with knee strength and has no impact on torque and work production during maximal concentric isokinetic knee muscle action in university-level female modern dancers.
Keywords: VERTICAL JUMP; PERFORMANCE; INJURIES; STIFFNESS; FITNESS; PLAYERS; SPRINT; RISK